THE DEVELOPMENT OF SPEAKING TEACHING MATERIAL WITH PROJECT BASED LEARNING FOR PACKET C AT PKBM ALVITA RAHMA - Firsta Malyda Putri; Leroy Holman Siahaan; Dini Hidayati (PT. Hasba Edukasi Mandiri, 2026)
English speaking skills are an important aspect for the general public to get a job. For people who have difficulty continuing their education, PKBM is a forum that aims to develop abilities and skills to improve their quality of life. People who choose to continue their studies to obtain a diploma equivalent to high school (Packet C) have an age range that is variably older than the age of students who attend high school in general, therefore this research aims to improve fluent English speaking skills by applying project based learning This method is expected to make it easier for PKBM Packet C teachers and students to learn creatively and innovatively so that students are expected to be able to practice soft skills at work. The urgency of this research is the availability of educational products, namely speaking teaching materials with project based learning for PKBM packet C schools, so that graduates from PKBM package C have superior graduate quality in the world of work to improve their quality of life. This research uses Research and Development (R&D) with the ADDIE development model which consists of 5 stages, namely Analyze, Design, Develop, Implement, Evaluate. Using data collection techniques using interviews, questionnaires, and documentation, then validation was carried out by 3 experts, namely material experts, media experts, and linguist experts. Based on the results of research on the development of speaking teaching materials for packet C PKBM, the results of the development were obtained. Validation results by material experts obtained a result of ????̅ = 3.867, validation results by media experts obtained a result of ????̅ = 3.76, validation results by language experts obtained a result of ????̅ = 3.9. The results of the questionnaire by the English subject teacher obtained a result of ????̅ = 3.67 and questionnaire results by PKBM packet C students ????̅ = 3.8. Evaluation of the post test results on 15 PKBM packet C students showed that 13 of the 15 students were declared complete, and from the overall results it was stated that 78.8% of students had completed/successfully.